A huge retroperitoneal liposarcoma mimicking ovarian teratoma: A case report - Jahan, Uruj; Gupta, Neena; Yadav, Rashmi; Fatima, Noor (Indian Journal of Case Reports, 2024)
Retroperitoneal liposarcoma is a malignant, primitive, and rare mesenchymal tumor. It can grow usually asymptomatic until large enough to compress the surrounding organs. We report an observation of a retroperitoneal liposarcoma mimicking an ovarian tumor. A 50-year-old, P1+0 postmenopausal female, presented to our Department of Obstetrics and Gynecology, with abdominopelvic mass and pressure symptoms for 2 months. Her magnetic resonance imaging abdomen and pelvis, ULTRASOUND-guided fine needle aspiration cytology, and tumor markers were done to make the provisional diagnosis after which, the patient underwent exploratory laparotomy. Complete removal of mass along with the right ovary was done in spite of mass encasing the right iliac vessels and the right ureter. Along with this, a hysterectomy with the left salpingo-oophorectomy and the right salpingectomy were done. A very huge ovarian tumor 22×15×28 cm weighing 5.5 kg was removed. Histopathological examination showed myxoid/well-differentiated liposarcoma with heterologous differentiation. Retroperitoneal liposarcomas are rare; however, they require an aggressive surgical approach, including multi-organ resection, if necessary, or multiple resections in the case of recurrence.